Unusual changes in the U.S. Treasury security market during the fourth round of quantitative easing - Kyle D. Allen; Scott E. Hein (Journal of Central Banking Theory and Practice, 2023)
The Covid-19 Pandemic and policy response rattled the USTreasury markets. Conventional US Treasuries, inflation adjustedUS Treasuries, and the relationship between the two developed inways such that ignoring changes in real interest rates yielded dis-torted inflation expectations estimates. Since the beginning of thepandemic, monetary policy kept nominal rates low and close tozero, but positive. Real rates, on the other hand, became increasing-ly negative. The relationship between the two market rates becamenegatively correlated, and distorted because of the fourth round ofquantitative easing, along with the Fed preventing nominal yieldsfrom turning negative. Federal Reserve actions during the Covid-19pandemic drove a larger wedge between nominal interest rates andreal interest rates in the inflation adjusted market.
Keywords: E4; E5; G21; G23; G28; 330; US Treasuries; Break Even Rate; Inflation; TIPS; Federal Reserve